Proceedings of the 45th IEEE Conference on Decision and Control 2006
DOI: 10.1109/cdc.2006.377155
|View full text |Cite
|
Sign up to set email alerts
|

Kinematic Modeling and Control of Robot Manipulators via Unit Quaternions: Application to a Spherical Wrist

Abstract: Unit quaternions have become a useful tool for describing rotations in space. This paper shows the application of unit quaternions (also called Euler parameters) to solve the problem of modeling and control of robot manipulators. First, a quaternion-based algorithm that allows to obtain the direct kinematic model of serial manipulators from the Denavit-Hartenberg parameters is introduced. This method is an alternative to the traditional one using homogeneous matrices. Then, a novel kinematic controller that us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 13 publications
0
14
0
2
Order By: Relevance
“…Typically, in robotic applications the propagation of orientation uncertainty is defined as the propagation along different joints (encoders) on a kinematic chain, or in the context of dynamic control the propagation of orientation uncertainty is defined when the orientation at time k + 1 depends on noisy orientation measured at time k [1,2]. In contrast, here we are interested in the static configuration where a fixed orientation of a rigid body is repeatedly measured in the same experimental conditions.…”
Section: Introductionmentioning
confidence: 97%
“…Typically, in robotic applications the propagation of orientation uncertainty is defined as the propagation along different joints (encoders) on a kinematic chain, or in the context of dynamic control the propagation of orientation uncertainty is defined when the orientation at time k + 1 depends on noisy orientation measured at time k [1,2]. In contrast, here we are interested in the static configuration where a fixed orientation of a rigid body is repeatedly measured in the same experimental conditions.…”
Section: Introductionmentioning
confidence: 97%
“…By taking the time derivative of (14) and (15), employing (2) and certain properties of skew-symmetric matrices (Campa et al, 2006), it can be shown that (Siciliano et al, 2010) e…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, the representation using unit quaternions, which is employed in this work, constitutes a singularity-free orientation representation, without complicating the control design. Unit quaternions are employed in (Campa et al, 2006;Caccavale et al, 2000Caccavale et al, , 2008Aghili, 2011) for manipulation tasks and in (Erhart and Hirche, 2016) for the analysis of the interaction dynamics in cooperative manipulation.…”
Section: Introductionmentioning
confidence: 99%
“…It has been applied to a spherical wrist, a manipulator, an underwater vehicle, etc. for set-point regulation [13], [14], [15]. There are papers on redundant manipulator control using quaternion.…”
Section: Introductionmentioning
confidence: 99%